KONSTRUKSI MEDIA BERITA ONLINE TERHADAP PEMBERITAAN PEREMPUAN (Analisis Framing okezone.com dan kompas.com terhadap Pemberitaan Perempuan dalam Kasus Korupsi Impor Daging Sapi) - , Kartika Suci Lestari Parhusip ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of this online news media is dynamic in the world of journalism. Online news media is now becoming one of the sources for the community in getting information. Realtime aspect in online news media is one of the advantages of online news media so as to meet the information needs of the community. Coverage of women in the beef import corruption case coloring mass media in Indonesia during the years 2013 Even beef import corruption case this is one case that has the highest rank in the news throughout 2013, The interesting thing about this case, the mass media in this media online news not just preach about corruption cases, but also reported on the emergence of the women allegedly involved in a corruption case beef imports. Coverage of women in the corruption case of beef imports is likely to provide a label for women who reported in this case.This study uses content analysis of media framing techniques Robert N.Entman models and Urs Dahinden. By using these framing techniques, this study aims to determine how the news frames of women in the beef import corruption case shown in okezone.com and kompas.com. The analysis was performed based on the theme of framing the substance which has been determined by researchers. Once analyzed, the contents of the news media and online news okezone.com kompas.com be examined to see the important findings in this study. Women reporting research data corruption beef imports is collected at month period January 2013 to June 2013 During this period okezone.com preach about women in corruption cases as much as 165 beef imports news and kompas.com preach as much as 134 news. Researchers will use customized news to the news theme of women who have been categorized so that the news that used in this study were 20 and 14 okezone.com news in kompas.com. In the visual images in this study were discussed in okezone.com 5 visual images and 3 visual images in kompas.com. This study concludes that the news media frame the news in the online news okezone.com define women in a corruption case beef imports this as a legal issue which also emphasizes the sexual gratification. While these women kompas.com defines news as legal issues that are not related to the problem of sex gratification. The role of women in this case consists of: women and money laundering, women and sexual gratification, and women in the trial witnesses and labeling aspects of women. In the news this online news media there are languages that are constructed in such a way by journalists. In framing the technical form of online news categories, news and kompas.com okezone.com women doing the news is dominated by the production of discourse categories realtime news.